2022
DOI: 10.2196/31471
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Health Game to Prepare Preschool Children for Anesthesia: Formative Study Using a Child-Centered Approach

Abstract: Background Every year, millions of children undergo medical procedures that require anesthesia. Fear and anxiety are common among young children undergoing such procedures and can interfere with the child’s recovery and well-being. Relaxation, distraction, and education are methods that can be used to prepare children and help them cope with fear and anxiety, and serious games may be a suitable medium for these purposes. User-centered design emphasizes the involvement of end users during the develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Accurate measurement of preoperative anxiety is essential for the care of pediatric surgery patients and for interventionist or educe their anxiety. The Yale Preoperative Anxiety Scale (YPAS) was developed in 1995 and modified (mYPAS) in 1997 to help measure the preoperative anxiety of children and was used in many studies including various health fields such as anesthesia, surgery, pediatrics, and dentistry (5)(6)(7)(8)(9)(10)(11)(12). In studies conducted in our country, the validity and reliability of the mYPAS-short form has also been demonstrated in Turkish children over the age of 2 (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate measurement of preoperative anxiety is essential for the care of pediatric surgery patients and for interventionist or educe their anxiety. The Yale Preoperative Anxiety Scale (YPAS) was developed in 1995 and modified (mYPAS) in 1997 to help measure the preoperative anxiety of children and was used in many studies including various health fields such as anesthesia, surgery, pediatrics, and dentistry (5)(6)(7)(8)(9)(10)(11)(12). In studies conducted in our country, the validity and reliability of the mYPAS-short form has also been demonstrated in Turkish children over the age of 2 (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no serious games have yet been developed to prepare children for the RT procedure. Further, researchers of serious game design have highlighted the significance of describing and reporting the involvement of end users in the design process and in research during the design process [ 21 ]. This paper is not primarily meant to point out the relevance of participatory design.…”
Section: Introductionmentioning
confidence: 99%
“…The animated handwashing instructions include all relevant handwashing steps (European Centre for Disease Prevention and Control 2020), including the wetting of hands and the various soaping movements (for selected animation screens see Figure 2). The design of the instruction and reward screens is based on previous studies of health games for children (Ingadottir et al 2022), and was confirmed through pre-tests with individual day care center children of different ages who provided feedback on the design. Furthermore, we pre-tested the digital system and the corresponding intervention to test if it is adequate to help us answer our research question.…”
Section: Design Of the Digital System And The Interventionmentioning
confidence: 99%